TESTING THE MEDIATION MODEL OF PERCEIVED ORGANIZATIONAL SUPPORT AND AFFECTIVE COMMITMENT IN THE RELATIONSHIP BETWEEN HUMAN RESOURCES PRACTICE AND EMPLOYEE ENGAGEMENT - Luturlean, Bachruddin Saleh; Praseti, Arif Partono; Saragih, Romat; Kurniawan, Erlangga Dwiki (International Journal of Psychosocial Rehabilitation, 2020)
Employee engagement is an important aspect for many organizations since it can affect their performance. Among various drivers of engagement are human resources (HR) practices, perceived organizational support, and affective commitment. Based on social exchange theory, we tested the mediation of perceived support and affective commitment in the relationship of HR practice and engagement. To test the model, we used data collected from 210 employees from private & the public sector in Bandung. The result shows positive correlation between the variables. Respectively, perceive support and affective commitment mediate the relation between HR practice and engagement. But, simultaneously they did not mediate the relationship. The overall effect is greater than the direct effect of HR practice on engagement.